Q: How do you solve y equals 2x-3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

-y + y equals 0.

x = -7, y = 2 ⇒ 2x3 + 15y = 2 x (-7)3 + 15 x 2 = 2 x (-343) + 15 x 2 = -656

For y - 2y - 3y equals 0, y equals 0.

y - 3 = 0 y = 3

Related questions

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

-y + y equals 0.

x = -7, y = 2 ⇒ 2x3 + 15y = 2 x (-7)3 + 15 x 2 = 2 x (-343) + 15 x 2 = -656

For y - 2y - 3y equals 0, y equals 0.

b = y - mx.

y= -2x

y - 3 = 0 y = 3

It can be simplified in the form of: 2x3+9x2-7x-34 = 0

y=x+4

y = -6

-3

y=5-x